Intercropping of greengram (Phaseolus radiatus), blackgram (P.mungo) and groundnut (Arachis hypogaea) with sunflower (Helianthus annuus) in rice-fallow coastal land - SARKAR, R K; KISHOR, S; CHAKRABORTY, A; BALA, B (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during the winter seasonÂ Â of 1992-93 and 1993-94 at Nimpith to evaluate the intercropping systems of pulse crops greengram (Phaseolus radialus 1.), blackgram (Phaseolus mungo L.) and oilseed crop groundnut (Arachis hypogaea L.) with sunflower (Helianthus annuus L.) in 2 planting patterns. Intercropping reduced the growth and yield attributes .and yield of component species compared with the respective pure stands but increased the plant height of the base crop. The seed yield of sunflower was higher in normal planting (45 cm) than in intercropping, but the total seed-equivalent yield of sunflower was the highest (2 646 kg/ha) in paired row (30-60 cm) sunflower + groundnufsystem. This treatment also gave the maxium land-equivalent ratio (1.44), monetary advantage (Rs 4 010/ha) and indicated modest competitive ratio (1.47 : 0.67), which proved the most efficient system.